A survey on fuzzy based game theory approaches for supply chain uncertainties in E-Commerce applications. (2022) - Praveena, S.; Prasanna Devi, S.
Abstract: The supply chain (SC) is supported in a decentralized form by many stakeholders, all pursuing different goals in e-commerce applications. In contrast the vast majority of studies on e-commerce supply chains use a centralized model and ignore the undesirable behaviors of stakeholders when making decisions. Fuzzy-based game theory for supply chain uncertainty management has undergone a detailed study of the literature to explore the many applications and recent breakthroughs. This study examines a dataset that comprises several articles on supply chain-made structures, surroundings, judgements, and game theory principles and implementations. Following is a three-part review: the creation and application in supply chain management analysis of the Nash and Stackelberg solution ideas, the integration of game theory fuzzy play at various supply chain topologies. Another objective of descriptive analysis is to describe the difference between changes in supply and demand. Using game theory ideas, the paper finishes with an assessment summary and suggestions for future supply chain analysis research.